Peran dan Kedudukan Dewan Gelar, Tanda Jasa Dan Tanda Kehormatan Dalam Sistem Ketatanegaraan Di Indonesia - Nurjannah Nurjannah (Media of Law and Sharia, 2022)
The aim of this study is to determine the role and position of the Dewan Gelar, Tanda Jasa dan Tanda Kehormatan (Dewan GTK) in the Administration System in Indonesia. The research method used is empirical normative research using a statutory approach. The results of the study found that Dewan GTK is a supporting institution or state auxiliary bodies or auxiliary institutions for executive power in the system of state administration in Indonesia. According to the theory of State Auxiliary Bodies (SAB), Dewan GTK includes Executive-Auxiliary, namely SAB that is included in the executive realm in general at the auxiliary level. In this category there are two different types of SAB functions which are to coordinate and to provide policy suggestions / recommendations to the President which based on its formation consists of two, namely, formed by the President and the second formed to represent certain groups to provide advice and input to the government. Dewan GTK is included as Auxiliary-Advisory, namely SAB which provides advice and considerations to the President.